![\left \{ {{x(5x-9) =y} \atop {5x-9=y}} \right. \left \{ {{x(5x-9) =y} \atop {5x-9=y}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%285x-9%29%20%3Dy%7D%20%5Catop%20%7B5x-9%3Dy%7D%7D%20%5Cright.)
x(5x-9) = 5x-9
x(5x-9) - (5x-9) = 0
(5x - 9)(x - 1) = 0
5x - 9 = 0
5x = 9
x = 1,8
x - 1 = 0
x = 1
5x - 9 = y | x = 1,8
9 - 9 = y
y = 0
5x - 9 = y | x = 1
5 - 9 = y
y = -4
5x^2 - 9x = y | x = 1,8
y = 16.2 - 16.2
y = 0
5x^2 - 9x = y | x = 1
5 - 9 = y
y = -4
OTBET: x = 1.8, x = 1; y = 0, y = -4